An application of the Analytical Hierarchy Process and Fuzzy Analytical Hierarchy Process in the selection of collecting centre location for the reverse logistics Multicriteria Decision-Making supply chain model. (10th July 2008) - Kannan, G.; Haq, A. Noorul; Sasikumar, P.
This paper aims at developing an effective and efficient Multicriteria Decision-Making (MCDM) model for selecting the collecting centre location in the Reverse Logistics Supply Chain Model (RLSCM) using the Analytical Hierarchy Process (AHP) and Fuzzy Analytical Hierarchy Process (FAHP). The paper aims at demonstrating how the model can help in solving such decisions in practice. The effectiveness of the model is illustrated using a case study taken in a tyre manufacturing industry located in the southern part of India and validated the results of AHP model using the result obtained from FAHP model. The proposed model helps the industry to select the collecting centre location effectively for the RLSCM.